Application potential of granite cutting waste and tunnel excavation rock as fine aggregates in cement-based materials based on surface characteristics. (15th December 2022) - Lin, Gaohang; Zhang, Lifeng; Cheng, Pengyun; Yu, Xing; Miao, Chuangbo; Qian, Kuangliang; Ruan, Shaoqin; Qian, Xiaoqian
Abstract: To alleviate the shortage of river sand (RS) and recycle abandoned resources, two recycled manufactured sands (RMSs) produced from tunnel excavation rock (tuff manufactured sand, TS) and granite cutting waste (granite manufactured sand, GS) are studied and compared with standard sand (SS) and RS. The aim is to identify the application potential of the two RMSs in cement-based materials. This is done by analyzing their influences on the mortar properties based on their surface characteristics and establishing a correlation between the surface characteristics of RMS and mortar properties. For the parent rock, petrographic analysis is performed and the uniaxial compressive strength is measured. For sand, the physical properties are evaluated and X-ray diffraction is used for analyzing the chemical composition. Digital image processing, nitrogen adsorption, and X-ray computed tomography are employed to determine the surface characteristics of sand particles. For the mortar, the fluidity, mechanical strength, water absorption, early total shrinkage, and accelerated expansion ratio are measured. The microstructure of the mortar interface transition zone is examined. Mercury intrusion porosimetry and thermogravimetric analysis are conducted to study the internal mechanism. The results indicate that compared with SS, the two RMSs reduce the fluidity of fresh mortar. In addition, TS is beneficial for the flexural, compressive, and tensile strengths of hardened mortar because of its denser internal pore structure and high degree of hydration caused by the properties of sand. The mechanical strength of the GS mortar can reach a similar or slightly higher level than that of the SS mortar. Furthermore, the fluidity and mechanical strength are well correlated with two parameters of sand, namely, roundness and specific surface area. The tensile strain capacity of the RMS-based mortar is superior to those of the SS and RS mortars. However, RMS increases the early total shrinkage. Although the TS mortar has the highest tensile strain capacity, it also has the largest early total shrinkage among the four mortar mixtures. Comparing the escalations in tensile strain capacity and early total shrinkage, the TS increases the risk of shrinkage cracking in the early stages. The effect of GS on the mortar tensile strain capacity is slightly greater than that on the early total shrinkage; thus, there is no significant influence on the risk of early shrinkage cracking in the GS mortar. In the accelerated expansion test, the TS shows potential alkali-silica reaction (ASR) risk in accordance with ASTM C1260, however, the GS indicates no potential for expansion damage. Based on the performance of various sands and mortars, GS has a better application value than TS. As for the TS mortar, it is necessary to consider the shrinkage cracking risk and ASR hazard in practical applications. Highlights: Application potential of granite cutting waste and tunnel excavation rock as fine aggregates is analyzed. The surface characteristics of sands are the focus of the discussion. Correlations between the surface characteristics of recycled manufactured sands and mortar properties are established. The risk of early shrinkage cracking of recycled manufactured sand mortar is studied.